PREDICTING INTENDED UNETHICAL BEHAVIOUR AMONG COLLEGE OF ECONOMICS AND BUSINESS STUDENTS: AN EMPIRICAL STUDY AT UNIVERSITAS GADJAH MADA - Winahjoe, Sari; Sudiyanti, Sudiyanti (Journal of Indonesian Economy and Business, 2014)
This study attempted to examine the intention to act in an unethical manner among theeconomics and business students in Universitas Gadjah Mada by applying the Theory ofPlanned Behaviour. Attitude, subjective norms, perceived personal outcome, perceived socialacceptance, and perceived behavioural control were included in predicting this intention. Atotal of 208 students participated in the main investigation. Using ordinal regression, 3hypothetical unethical situations were proposed to measure the studentsâ intended behaviour:(1) having the class attendance list signed by a classmate; (2) cheating in an examination orquiz; and (3) knowingly plagiarising someone elseâs work. The results confirmed that attitudewas the strongest predictor of a studentâs intention to act in an unethical manner. The studyfindings also supported subjective norms as the second strongest predictor, which was followedby perceived personal outcome and perceived social acceptance as determinants of suchbehavioural intention. Meanwhile, the findings demonstrated that perceived behavioural controlwas the weakest predictor of intention. Analysis for each situation, implications forpractitioners, specifically university teachers and education policy makers, and further researchrecommendations are also discussed.Keywords: theory of planned behaviour, course of ethics, education policy, behaviouralintention